2023
DOI: 10.3389/fpls.2022.1088220
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and metabolome analyses reveal that Bacillus subtilis BS-Z15 lipopeptides mycosubtilin homologue mediates plant defense responses

Abstract: Microbial-plant interactions protect plants from external stimuli, releasing various elicitor that activate the plants defense response and regulate its growth. Bacillus subtilis BS-Z15 was screened from cotton inter-rhizosphere soil, antagonized various plant pathogens, and protected cotton against Verticillium dahliae. This study showed that the BS-Z15 lipopeptide mycosubtilin homologue could act as an elicitor to induce systemic resistance (ISR) in plants. Mycosubtilin homologue induced ROS burst and deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Bacillus subtilis is one of the main sources of probiotics and is classified as GRAS (Generally Recognized as Safe) by the US Food and Drug Administration (FDA). This organism has remarkable biosynthetic potential [ 6 ] and secretes a variety of secondary metabolites such as enzymes and lipopeptides that exhibit broad-spectrum antimicrobial [ 7 ], anticancer [ 8 ], antinematicidal activities [ 9 ], and immune activation in plants [ 10 ] and animals ( 11 – 13 ). Lipopeptides act as immunomodulators by interacting with pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs), expressed on antigen-presenting cells (macrophages and dendritic cells) to activate immune functions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus subtilis is one of the main sources of probiotics and is classified as GRAS (Generally Recognized as Safe) by the US Food and Drug Administration (FDA). This organism has remarkable biosynthetic potential [ 6 ] and secretes a variety of secondary metabolites such as enzymes and lipopeptides that exhibit broad-spectrum antimicrobial [ 7 ], anticancer [ 8 ], antinematicidal activities [ 9 ], and immune activation in plants [ 10 ] and animals ( 11 – 13 ). Lipopeptides act as immunomodulators by interacting with pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs), expressed on antigen-presenting cells (macrophages and dendritic cells) to activate immune functions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, secondary metabolites of B. subtilis strain Z15 (BS-Z15) were found to be highly effective as a broad-spectrum antibacterial in vitro and could act as an elicitor to regulate systemic resistance in plants by inducing the immune response of plants [ 10 ]. Furthermore, in vivo studies demonstrated that BS-Z15 was safe and non-toxic in animals.…”
Section: Introductionmentioning
confidence: 99%
“…57 Our results suggest that plants enhance their immunity by synthesizing these hormones. Yang et al 58 found that Bacillus subtilis BS-Z15 lipopeptides mycosubtilin homologue mediate plant immunity by activating the Arabidopsis ISR through multiple PTI components and transcriptional metabolic pathways (MAPK signaling pathway, phytohormone signaling, etc.). This suggests that bacterial communities can influence plant growth and immunity through certain pathways that regulate transcriptional metabolic pathways in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The ISR-eliciting activity of CFCF was attributed to Bacillus sp.-secreted metabolites with antibiotic functions, such as iturinic-type lipopeptides, iturin A and bacilomycin D, as well as to the lipopeptides fengycin and surfactin [ 55 ]. In particular, it has been demonstrated that the spraying of A. thaliana leaves with iturin A or mucosubtilin activated the expression of SA and JA defense-related genes, PR1 and PDF1.2 [ 56 ], while A. thaliana seedling treatment with mycosubtilin from B. subtilis J-15 activated the expression of ET and JA defense-related genes [ 57 ]. Similarly, root treatment of tomato plants with fengycin stimulated the induction of SA-responsive genes [ 58 ].…”
Section: Discussionmentioning
confidence: 99%